Urgency of Providing Shares to Local Communities in Mineral and Coal Mining Activities - Rachmawati, Ani (Jurnal Konstatering, 2025)
Providing shares to local communities in mineral and coal mining activities is very important. The position of the community as a party that is very potentially harmed in mining activities, is something that cannot be avoided even though they are permanent residents and even all natural losses will have an impact on the community. This study aims to conduct a study and analysis of the importance of providing shares to local communities in mineral and coal mining activities. The formulation of the problem in this study consists of: First, How are the problems of local community welfare whose areas are areas of mineral and coal mining activities. Second, How is the urgency of providing shares to local communities in mineral and coal mining activities. The research method used is doctrinal legal research with a statutory and conceptual approach. The results of this study conclude that: First, the problems of local community welfare in mineral and coal mining are that there are extraordinary social impacts such as environmental damage and the emergence of economic disparities caused by the management of nickel and coal mining solely to improve the welfare of entrepreneurs. Second, so far, CSR in its implementation has not been able to improve the welfare of the people in the nickel and coal mining areas. This shows that it is time for the public to be given shares in every nickel and coal company, because only then will there be legal certainty to obtain prosperity.